Glacier-Surface Velocity Derived Ice Volume and Retreat Assessment in the Dhauliganga Basin, Central Himalaya – A Remote Sensing and Modeling Based Approach - Sattar, Ashim; Goswami, Ajanta; Kulkarni, Anil V.; Das, Pritam (Frontiers in Earth Science, 2019)
Himalayan glaciers are a storehouse of fresh water and play a significant role in influencing the runoff through numerous perennial rivers flowing over the Indo-Gangetic plains, providing freshwater to the second largest populated country in the world. For suitable management of this water resource, measurement of glacier-ice volume is extremely important in the current scenario of climate change and water scarcity. To address this concern, the present study endeavors to find a suitable methodology to quantify glacier volume and retreat in the Central Himalaya. Herein, two methods were implemented to estimate the total glacier ice volume – conventional area-based scaling method and glacier-surface velocity based modeling technique. The availability of field data allowed a validation assessment to be carried out on two Himalayan glaciers (Chhota Shigri and Satopanth). Here, we propose a volume-area power law, appropriate for the application in the context of Himalayan glaciers. The ice volume of 15 glaciers larger than 1 km2 calculated using a spatially distributed ice thickness model is 3.78 × 109 m3 (f = 0.8), with an overall uncertainty of 18.4%. The total volume of the remaining glaciers in the basin, calculated using a tuned volume-area scaling relation is 2.71 × 109 m3. A sensitivity analysis is performed to evaluate the influence of input parameters on the model and volume-area scaling performance. The study also incorporates investigation of the glacier bed topography for discrete identification of the overdeepening sites in the glacier valley which are potential lake formation sites in the future. A total of 54 overdeepening sites covering an area of 2.85 km2 have been identified. In addition, the relative glacier area loss of the glaciers is investigated using historical CORONA and Landsat satellite imageries. Glaciers with a smaller area and those with lower mean ice thickness near the terminus shrank significantly more, as compared to the larger ones. The total area of the selected larger glaciers is estimated to be 68 km2 in 2015 and deglaciation of 4.7 km2 is observed over the period of 48 years that accounts for 6.9% of the total area in 1968.